ANALISIS PENERAPAN MODEL PBL BERBANTUAN MEDIA STICK POUCH PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Natasya Zam Zam Firdaus; Kunti Diana Ayu Afiani; Badruli Martati (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
The purpose of the study was to describe the results of the application of the PBL model assisted by stick pouch media in learning mathematics in elementary schools. The type of research is descriptive qualitative, located at SD Muhammadiyah 17 Surabaya. The research subjects were class 1A students in the 2024/2025 school year, totaling 20 students. Triangulation data collection techniques, with data collection techniques carried out using observation, interviews, and questionnaires. Data analysis used Milles and Huberman analysis, namely data reduction, data presentation, and drawing conclusions. The results showed that the application of the PBL model assisted by stick pouch media, students were enthusiastic in listening and listening to the teacher when explaining the learning objectives, in the delivery of material and enthusiastic in answering questions or questions given by the teacher. When using stick pouch media, students are very enthusiastic and want to immediately use stick pouch media. Response questionnaires from teachers and students related to the application of the PBL model assisted by stick pouch media in learning mathematics can make it easier to convey addition material and students are easy to understand the material and learning becomes fun.